2015
DOI: 10.1097/igc.0000000000000506
|View full text |Cite
|
Sign up to set email alerts
|

Niclosamide Analogs for Treatment of Ovarian Cancer

Abstract: The niclosamide-like analogs produced cytotoxicity both alone and in combination with carboplatin against tumorspheres from patient ascites and slices from solid tumor samples. Tumor slices showed similar cytotoxicity to matched ascites samples. Western blots showed down-regulation of Wnt pathway-associated proteins in patient samples treated with niclosamide analogs. These results suggest that more soluble niclosamide analogs may be useful for the treatment of ovarian cancer in combination with chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…In accordance with these findings, our previous results revealed the same relation between the toxicity of ring-substituted hydroxynaphthanilides to the THP-1 cancer cells and the presence of substituents with electron-withdrawing properties [3,4,5]. The SAR studies also found the presence of an electron-withdrawing nitro group to be one of the essential requirements for the anticancer effect of niclosamide [21]. Based on these findings, the substitution by a nitro moiety was determined to be appropriate for the potent anticancer effect of newly-designed hydroxynaphthanilides.…”
Section: Introductionsupporting
confidence: 77%
“…In accordance with these findings, our previous results revealed the same relation between the toxicity of ring-substituted hydroxynaphthanilides to the THP-1 cancer cells and the presence of substituents with electron-withdrawing properties [3,4,5]. The SAR studies also found the presence of an electron-withdrawing nitro group to be one of the essential requirements for the anticancer effect of niclosamide [21]. Based on these findings, the substitution by a nitro moiety was determined to be appropriate for the potent anticancer effect of newly-designed hydroxynaphthanilides.…”
Section: Introductionsupporting
confidence: 77%
“…Several other groups have also shown that niclosamide and niclosamide derivatives can inhibit mTOR and STAT3 signaling in various tumor types [1319]. We previously showed that niclosamide and its analogs were anti-proliferative and targeted the Wnt pathway in >30 primary ovarian cancer patient ascites samples, some of which were clinically platinum resistant [12, 20]. In addition, we found that niclosamide specifically decreased the stem cell marker ALHD1A1 and the Wnt pathway surface receptor LRP6.…”
Section: Introductionmentioning
confidence: 77%
“…A schematic is shown in Figure 1 of the Haygood et al . manuscript [12]. Carboplatin was purchased from Sigma-Aldrich (St. Louis, MO), dissolved in water at concentration of 25 mM, and stored at 4°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study indicates that Niclosamide may also exert its anticancer activity through inhibition of Wnt/β-catenin target gene FGF1 in ovarian cancer [32]. More recently, efforts have been devoted to developing Niclosamide analogs with higher bioavailability [77] and/or designing more efficacious formulations for preclinical and eventually clinical studies [78].…”
Section: Discussionmentioning
confidence: 99%